AN ATTEMPT TO IMPROVE STUDENTS' HEALTH LITERACY SKILLS WITH BLOODYPEDIA BASED ON PROBLEM-BASED LEARNING ON CIRCULATORY SYSTEM MATTERS - Putri, Aulia; Weliyanti, Amanda; Rusdi, Rusdi; Hendi Ristanto, Rizhal; Setyo Rini, Daniar; Suryanda, Ade (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
Health literacy is the capacity to obtain, process, and comprehend fundamental health information and health services that facilitate the formulation of informed health decisions. The objective of this study is to enhance students' health literacy abilities by employing problem-based learning media on circulatory system content. The Classroom Action Research method, employing a cyclic research model comprising two cycles with four stages—namely, planning, action, observation, and reflection—is expected to facilitate the improvement of health literacy skills among class XI students. The CAR methodology employs problem-based learning, which is conducted with 36 students. The data collection method employs test scores or scores on pre- and post-test health literacy questionnaires containing 10 questions, which will be compared on average as a reference for improving students' health literacy. The findings of this study indicate that there was an increase in health literacy skills, with a value of 13.86% in Cycle I and 13.96% in Cycle II. In conclusion, the results of this action research demonstrate that the problem-based learning model with Bloodypedia media is an effective method for improving the health literacy skills of grade XI students on the material of the human circulatory system. Keywords: Bloodypedia, health literacy, problem-based learning